Mercedes García-Arenal, Gerard Wiegers, Ryan Szpiech (Eds.): Interreligious Encounters in Polemics between Christians, Jews, and Muslims in Iberia and Beyond. Leiden: Brill, 2019, 343 pp. ISBN: 978-90-04-40176-1. - Herrera-Vicente, Javier (Philologia Hispalensis, 2023)
Reseña del libro: Interreligious Encounters in Polemics between Christians, Jews, and Muslims in Iberia and Beyond